Transformasi kemampuan analisis statistik mahasiswa UIN Mataram melalui pelatihan software JASP - Ghazali, Muhammad; Zohri, Muhammad; Lestari, Juwita; Purnamasari, Ramdani; Fitriati, Ita (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2023)
Statistical data analysis is the process of examining, cleaning, transforming, and modeling data with the aim of discovering useful information, drawing conclusions, and supporting decision-making. This process involves various statistical techniques and methods applied to data to understand, explain, and predict phenomena. Skills like these are greatly needed by students. Therefore, training in the use of the open-source statistical application JASP is necessary to enhance the statistical data analysis capabilities of UIN Mataram students, especially those in their final semester. This community service activity aims to introduce and train the use of JASP as a free and license-free alternative for statistical data analysis, considering the limitations of accessibility and ethical issues surrounding the use of paid software like SPSS in academic environments. The training methodology includes theoretical sessions and practical application of JASP, focusing on multiple linear regression analysis and path analysis. An initial survey showed that only 25% of final-semester students were familiar with open-source applications like JASP. After the training, there was a significant increase in understanding and application of JASP, with 85% of participants showing improved competence. These results demonstrate the importance of training in open-source statistical applications to support student academic research and strengthen academic integrity within the Islamic university environment. This study provides insights into ethical and affordable statistical software alternatives and highlights the importance of analytical skills in higher education.